2018
DOI: 10.1080/13639080.2019.1569212
|View full text |Cite
|
Sign up to set email alerts
|

Construction of ethnicity, immigration and associated concepts in Swedish vocational education and training

Abstract: Surges of migration into Sweden and other European countries have raised needs to adjust civic education to provide Bernsteinian pedagogic rights of enhancement, participation and inclusion, both generally and in VET specifically. However, associated issues have received little research attention even in countries with colonial histories and longer traditions of immigration and non-native ethnic minorities. Moreover, most published empirical studies on race and ethnicity issues in VET have had Anglophone setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The most expressed criticism was that the guidance should have been more specific' (MEAE 2020b: 5). Studies also show how refugees and immigrants struggle more than any other unemployed group (Jervelund, Krasnik & De Lasson 2020) and how guidance and teaching do not tackle racism in services or integration practices (Masoud, Holm & Brunila 2019, see also Rosvall et al 2019 on the Swedish context).…”
Section: Integration Policy and Practices In Finlandmentioning
confidence: 99%
“…The most expressed criticism was that the guidance should have been more specific' (MEAE 2020b: 5). Studies also show how refugees and immigrants struggle more than any other unemployed group (Jervelund, Krasnik & De Lasson 2020) and how guidance and teaching do not tackle racism in services or integration practices (Masoud, Holm & Brunila 2019, see also Rosvall et al 2019 on the Swedish context).…”
Section: Integration Policy and Practices In Finlandmentioning
confidence: 99%
“…When the role of civic education in vocational preparation programmes has been examined, the studies have more often been based on different educational sociology perspectives (cf. Holtsch et al, 2019;Ledman et al, 2018;Rosvall et al, 2018). In both these and in the less frequent cases, where the more general pedagogical aspects of the civic function and emancipatory potential of vocational education have been studied, the aim has usually been to examine the qualifying and socialising effects of the teaching (cf.…”
Section: Previous Researchmentioning
confidence: 99%
“…Taking a student perspective, several studies have also found that VET students would like to learn more about politics (Ledman 2015), structural inequalities based on gender (Brunila and Ylöstalo 2015) and ethnicity (Rosvall et al 2018;Rosvall and Öhrn 2014), and how to exert influence and exercise active citizenship (Furlong 2009). However, European cross-country studies have shown that VET includes little education in political and historical issues (Ledman 2015), and stimulates less political participation than academic education (Persson 2012).…”
mentioning
confidence: 99%